2014
DOI: 10.1002/chem.201304042
|View full text |Cite
|
Sign up to set email alerts
|

Methane Activation by Diatomic Molybdenum Carbide Cations

Abstract: Metal carbide species have been proposed as a new type of chemical entity to activate methane in both gas-phase and condensed-phase studies. Herein, methane activation by the diatomic cation MoC(+) is presented. MoC(+) ions have been prepared and mass-selected by a quadrupole mass filter and then allowed to interact with methane in a hexapole reaction cell. The reactant and product ions have been detected by a reflectron time-of-flight mass spectrometer. Bare metal Mo(+) and MoC2H2(+) ions have been observed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
43
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 101 publications
0
43
0
Order By: Relevance
“…Only a few oxide species such as FeO + , [6,15] CoO + , [16] and NiO + [17] can react with methane to produce stable C 1 oxygenates methanol and formaldehyde. [2,3] It is noteworthy that in addition to oxides, oxygen-free species including atomic transition metal ions, [18] Au 2 + , [19] MoC + , [20] and so on [3,21] can also react with methane to generate stable molecules such as C 2 H 4 and H 2 .…”
mentioning
confidence: 99%
“…Only a few oxide species such as FeO + , [6,15] CoO + , [16] and NiO + [17] can react with methane to produce stable C 1 oxygenates methanol and formaldehyde. [2,3] It is noteworthy that in addition to oxides, oxygen-free species including atomic transition metal ions, [18] Au 2 + , [19] MoC + , [20] and so on [3,21] can also react with methane to generate stable molecules such as C 2 H 4 and H 2 .…”
mentioning
confidence: 99%
“…1532, 1533) were observed by solid-state NMR after treatment of silica-bound carbyne complexes 1530, 1531 with trimethylphosphine [1316]. A computational study of molybdenum carbide catalyzed conversion of methane to ethylene or acetylene evoked several C-H activation of alkyl and hydride migration steps [1317]. As previously noted in the discussion of Group 6 metal carbene complexes, carbyne complex intermediates are involved in the transformation of silylene complexes to cyclic carbene complexes using episulfides [920].…”
Section: Page 184 Of 218mentioning
confidence: 89%
“…15) has a large SD value of 1.59μ B , which corresponds to a significant overall activation barrier (0.10 eV). This study revealed that to cleave the C-H bonds through the OA mechanism, the unreactive ETM centers can be properly engineered to be reactive through carburization, 233,236 which explains the importance of the related metal carbides in heterogeneous catalysis. The dissociative-adsorption of CO onto Mo 2 C 2 − thus correctly manipulates the SD distribution on the metal centers and promotes the activation and transformation of methane.…”
Section: Reaction With Organic Substratesmentioning
confidence: 95%